St. Nicholas Collegiate Church, south transept, east wall, Joyce tomb, base - O'Donovan, Danielle (My University, 2008)
Base of tomb niche jamb. Moulding comprises from top down: grooved roll, bell, flat surface at right angle, hollow chamfer, quadrant, flat surface, bell, flat surface at right angle, quadrant, hollow chamfer, plinth. The mouldings here are unusual, the two lower elements protrude from the bell as two square blocks with mouldings at their front face.
Joyce tomb
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Funerary Monuments; Architecture, Franciscan; Late Medieval; roll moldings; moldings, hollow